Environmental characterization of a filling station from the standpoint of environmental adaptation (Research, Society and Development, 2020)
As such, the aim of this study was to characterize the environmental situation of a filling station in Mossoró, Rio Grande do Norte state, Brazil, from the standpoint of adapting to current environmental regulations. Next, an exploratory-descriptive case study was carried out at one of the filling stations of the city, where the problem was more serious. The results revealed that the station installed an overfill protection containment chamber in the fuel storage tanks, in order to avoid leaks. However, the environment was partially inadequate due to the inefficiency of the oil-water separator system, damage to contention chamber pumps and filters and unsuitable final destination for class 1 waste, considered dangerous to the environment and public health, especially nearby inhabitants. In addition, there is no continuous monitoring by the environmental licensing department. It is therefore recommended that interventions aimed at sustainability of the filling station be implemented by the licensing entity.